Correlation of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio and carcinoembrionic antigen level in colorectal cancer - Candrawati, Oktania; Utomo, Bambang Eko Broto Hari; Sofii, lmam (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Colorectal cancer is one of cancer that has a high mortality rate. Cancer is associated with a systemic inflammatory response. Carcinoembryonic antigen (CEA) is a colorectal cancer prognostic marker, but this examination is quite expensive and not always ubiquitously available. Therefore, systemic inflammatory markers through routine blood examination are expected as a colorectal cancer marker. Objective: The present study is to determine a correlation of neutrophil-lymphocyte ratio (NLR), the platelet-lymphocyte ratio (PLR), the lymphocyte-monocyte ratio (LMR) and CEA level in colorectal cancer patients. Methods: This retrospective cross-sectional study was conducted in November 2016-January 2017 at Dr. Sardjito Hospital, Yogyakarta. As many as 209 patients who underwent surgery in January 2015-Decemberr 2016 with colorectal cancer histopathologic diagnosis were included. Demographic, clinical, histopathology and preoperative NLR, PLR, LMR and CEA level was obtained from medical records. Correlation of NLR, PLR, LMR and CEA level was analyzed with Somer’s test. Result: As many as 51.2% of subjects were male. Most subjects (n 42.6%) were diagnosed at 45-60 years old. The most common location of the tumor is in rectum (65.1%). Histopathology examination showed well differentiation in 51.7% subjects. The Somer’s analysis showed there was correlation of NLR and CEA level (p=0.023, r=0.164), there was a correlation between PLR and CEA level (p=0.016, r=0.146). Higher NLR and PLR was proportional to higher CEA level. There was a correlation of LMR and CEA level (p=0.001, r=-0.188), lower LMR correlates to higher CEA level. Conclusion: There is significant positive correlation of NLR and CEA level, PLR and CEA level, and negative correlation of LMR and CEA level in colorectal cancer patients.